Trace element content in soils of the King George and Elephant islands, maritime Antarctica. Issue 9 (21st October 2017) - Abakumov, E.; Lupachev, A.; Andreev, M.
ABSTRACT: Trace element concentrations were studied in soils of the King George and Elephant islands in the maritime part of West Antarctica. The lowest concentrations of Cu, Pb, Cd, Zn, Ni and Mn were typical for the pristine soil of Elephant Island. The highest concentrations of these elements were found in the Fildes Peninsula and revealed the influence of human activities in the area of the Bellingshausen station and adjacent waste disposal sites. Ornithogenic soils of the Fildes Peninsula have shown low concentrations of Cd and As. Using geoaccumulation indexes, all the pristine soils of King George and Elephant islands and ornithogenic soils of the Fildes Peninsula were classified as unpolluted; the human-affected soils were mainly identified as moderately polluted. Obtained data can be used as background concentration levels for further researches. GRAPHICAL ABSTRACT: